2008
DOI: 10.1111/j.1365-2141.2008.07132.x
|View full text |Cite
|
Sign up to set email alerts
|

Relapse prediction in acute myeloid leukaemia patients in complete remission using WT1 as a molecular marker: development of a mathematical model to predict time from molecular to clinical relapse and define optimal sampling intervals

Abstract: Summary We hypothesized that Wilms tumour 1 gene (WT1) expression levels in acute myeloid leukaemia (AML) patients might have predictive value and reveal molecular relapse kinetics. WT1 level was determined at diagnosis, during therapy and post‐therapy follow‐up in 89 patients who reached first complete remission (CR1) (952 samples, median 8 samples/patient, range 2–38). CR1 bone marrow (BM) WT1 level above normal (based on 39 healthy donors) was an independent adverse prognostic factor regarding both disease‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 33 publications
2
91
0
1
Order By: Relevance
“…59 Furthermore, the significance of normalized WT-1 expression levels post induction therapy was less clear, as 21 of 48 these patients relapsed. These findings are supported by Ommen et al 60 The available studies indicate that WT-1 levels above normal levels, which may be seen in normal regenerating marrow, are associated with subsequent relapse. These data are supported by finding them to correlate with disease-specific fusion gene transcript numbers.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 79%
“…59 Furthermore, the significance of normalized WT-1 expression levels post induction therapy was less clear, as 21 of 48 these patients relapsed. These findings are supported by Ommen et al 60 The available studies indicate that WT-1 levels above normal levels, which may be seen in normal regenerating marrow, are associated with subsequent relapse. These data are supported by finding them to correlate with disease-specific fusion gene transcript numbers.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 79%
“…WT1 mRNA from PB detected MRD more sharply than the morphological findings of bone marrow aspiration. It has been reported that WT1 mRNA expression is a general molecular marker in leukemia (Inoue et al 1996;Cilloni et al 2002Cilloni et al , 2004Cilloni et al , 2008Lapillonne et al 2006;Ommen et al 2008). It is important to measure WT1 mRNA at any time, at diagnosis or in CR.…”
Section: Discussionmentioning
confidence: 99%
“…This approach requires the selection of a specific peptide epitope. In general, to enhance antigen immunoreactivity, the peptide should have strong hydrophilicity and a stable conformation, and either end of the peptide should be linear to maximize its availability for antibody binding (5,7). Using this criterion, we selected a 14-amino acid sequence (CALWVSGIFVDEVI) at the N-terminus of the FAMLF protein that was predicted to have high hydrophilicity, be readily accessible to antibody, and be specific to FAMLF, thereby reducing the likelihood of non-specific binding.…”
Section: Discussionmentioning
confidence: 99%